2017
DOI: 10.1080/08898480.2016.1271650
|View full text |Cite
|
Sign up to set email alerts
|

Representativeness in panel surveys

Abstract: A panel is a set of units recruited and used in successive surveys. When the sample unit is the household, so-called R-indicators together with the comparison of distributions of certain variables to those known in the total population help to measure the representativeness of the panel. The method is applied to Understanding Society, a UK household longitudinal study.At each wave, under-and over-represented groups of individuals are identified. This allows the implementation of better survey designs and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Postcards buyers still exist; generally they are computer illiterate people or children (Gilli and Pedrotti, personal communications), so postcard buyers after the year 2010 would not be a representative sample of the population. This is known in the marketing sector, as online surveys are more likely to reach the new generations compared to older people with limited access to the Internet [48].…”
Section: Cultural Es: Aesthetic Value From Postcardsmentioning
confidence: 99%
“…Postcards buyers still exist; generally they are computer illiterate people or children (Gilli and Pedrotti, personal communications), so postcard buyers after the year 2010 would not be a representative sample of the population. This is known in the marketing sector, as online surveys are more likely to reach the new generations compared to older people with limited access to the Internet [48].…”
Section: Cultural Es: Aesthetic Value From Postcardsmentioning
confidence: 99%
“…R-indicators can also be used as indicators for representativeness in panel studies (Schouten et al 2012). Bianchi and Biffignandi (2017) used R-indicators to compare the panel sample of the UK household longitudinal study Understanding Society over waves with administrative data to assess population representativeness. In sum, they showed that R-indicators were a valuable measure of representativeness.…”
Section: Analytical Approachmentioning
confidence: 99%
“…Attrition rates are highest at the second wave and then tend to decline over time (Lugtig 2014;Schoeni et al 2013;Uhrig 2008). There is also evidence that the correlates of nonresponse may change over waves of a survey (Farrant and O'Muircheartaigh 1991) and that changes in correlates of nonresponse at each subsequent wave are lower compared to the previous one (Bianchi and Biffignandi 2017a).…”
Section: Introductionmentioning
confidence: 99%